ICT integration in teaching and learning: Perceptions and practices in Ghanaian college of education - Asare, Samuel; Emmanuel, Mensah Kwadwo; Dankwah, Emmanuel Appiah; Eric, Abrefah-Mensah (International Journal of Educational Technology and Learning, 2023)
This research study investigates the perceptions and practices of Information and Communication Technology (ICT) integration in teaching and learning within Ghanaian Colleges of Education. With the increasing recognition of ICT as a valuable tool in education, it is crucial to understand how these technologies are being utilized in the context of teacher training institutions, specifically in Ghana. The research employs a qualitative data collection method. Semi-structured interviews were conducted to gather comprehensive insights into the perceptions and practices of ICT integration among college faculty and students. The participants include teacher educators, and pre-service teachers in Ghanaian College of Education. Through thematic analysis, the qualitative data provide a deeper understanding of various stakeholders’ attitudes, beliefs, and perceptions toward ICT integration. The findings of this study contribute to the existing body of knowledge on ICT integration in teaching and learning in Ghanaian College of Education. It will shed light on the current practices, challenges faced, and potential opportunities for improvement. The research outcome can inform policy decisions, curriculum development, and professional development initiatives to enhance ICT integration within teacher training programs in Ghana. By addressing the perceptions and practices surrounding ICT integration, this study aspires to support the transformation of teacher education, leading to more proficient and technologically equipped educators prepared for the 21st-century classroom challenges.